A Review of Sensor Technologies Applicable for Domestic Livestock Production and Health Management - Bimrew Asmare (Advances in Agriculture)
The world is running for the digitalization of social, economic, and political endeavors. As the world is getting into technologies of various streams of development, agriculture, especially livestock production, is also one of the areas of development that requires the application or use of emerging technologies. But knowledge and skill are relatively scanty, particularly in developing countries. Hence, it is vital to fill this gap of knowledge by compiling information and presenting it to a large audience for further research in the field. In the era of the advent of sensors for broader fields, it is important to consider the possible application of these technologies in rangeland condition assessment and animal production. The technologies are more relevant in the implementation of precisions farming practices of livestock including the individual animal behavior, grazing condition, health condition, and forage intakes. For grazing stock, it is vital to assess the status of both livestock grazing behavior and rangeland resource conditions. The rangeland resources are important components of livestock production throughout the world. Forages and pasture are dynamics in the abundance, species composition, and chemical composition as a result of environmental and management changes. The rangeland resources must be assessed and monitored for better management and utilization. Conventional assessments which include manual or mechanical counting, identification, and chemical composition are laborious and time-consuming. Under field conditions, not only grazing lands condition can be monitored using sensors but also is possible to understand the grazing behavior of animals for better management of grazing stock. To complement and or replace conventional techniques, it is vital to understand the current technologies such as sensors or biosensors. This review study is organized to increase awareness of the available technologies and their relevance regarding rangeland resources, particularly in tropical rangelands. In most cases, in the tropics, GPS systems are commonly used to assess only the rangeland status without considering the grazing stock. The review also elucidates that sensor technologies are important to detect livestock health conditions and movements at the field level in a rapid and easy way. However, like other technologies, sensors (biosensors) have limitations including accuracy of measurements and repetitive data accusations. Nevertheless, the review elucidates the use of sensor technologies and saves time and energy in animal production which otherwise could demand extensive energy and time.